Aggregate Risk and the Choice between Cash and Lines of Credit - ACHARYA, VIRAL V.; ALMEIDA, HEITOR; CAMPELLO, MURILLO (Journal of Finance, 2013)
ABSTRACT Banks can create liquidity for firms by pooling their idiosyncratic risks. As a result, bank lines of credit to firms with greater aggregate risk should be costlier and such firms opt for cash in spite of the incurred liquidity premium. We find empirical support for this novel theoretical insight. Firms with higher beta have a higher ratio of cash to credit lines and face greater costs on their lines. In times of heightened aggregate volatility, banks exposed to undrawn credit lines become riskier; bank credit lines feature fewer initiations, higher spreads, and shorter maturity; and, firms’ cash reserves rise.